Discovery and optimization of oxadiazole-based FLAP inhibitors. Issue 20 (15th October 2017) - Bartolozzi, Alessandra; Abeywardane, Asitha; Bosanac, Todd; Broadwater, John A.; Chen, Zhidong; Hutzler, J. Matthew; Huber, John D.; Nemoto, Peter; Olague, Alan; Riether, Doris; Simpson, Tom; Takahashi, Hidenori; et al.
Graphical abstract: Abstract: Structure activity relationship (SAR) investigation of an oxadiazole based series led to the discovery of several potent FLAP inhibitors. Lead optimization focused on achieving functional activity while improving physiochemical properties and reducing hERG inhibition. Several compounds with favorable in vitro and in vivo properties were identified that were suitable for advanced profiling.